2022
DOI: 10.1007/s40544-021-0560-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high-stability Ni-PSF@PAO40 microcapsules and their lubricating properties in polyamide 6

Abstract: Novel Ni-PSF@PAO40 microcapsules (NPPMS) with high stability were prepared by using a combined processing method of electroless nickel plating and solvent volatilization. The results indicate that Ni is completely assembled on the surfaces of PSF/PAO40 microcapsules with the encapsulation capacity of NPPMS achieved at 50%. Organic solvents immersion shows that NPPMS have an excellent chemical stability. Macro thermal stability tests reveal that the softening temperature of NPPMS is increased up to over 400 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…9. Firstly, the microcapsules in the PVDF composite rupture under the action of load and frictional contact during the sliding process, and the encapsulated lubricating oil is then released to the friction surface and forms an oil lubricating lm [32,37,[39][40][41]. This oil lubricating lm helps to separate the contact surfaces, thereby reducing the friction coe cient and wear rate.…”
Section: Antifriction and Wear Mechanisms Of Pvdf Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…9. Firstly, the microcapsules in the PVDF composite rupture under the action of load and frictional contact during the sliding process, and the encapsulated lubricating oil is then released to the friction surface and forms an oil lubricating lm [32,37,[39][40][41]. This oil lubricating lm helps to separate the contact surfaces, thereby reducing the friction coe cient and wear rate.…”
Section: Antifriction and Wear Mechanisms Of Pvdf Compositesmentioning
confidence: 99%
“…Among them, microcapsules containing lubricating oil are well known as a novel core-shell additive that enables the incorporation of lubricating oil into polymer matrices. Many related studies have reported that microcapsules have amazing effects in enhancing the tribological properties of polymers, such as epoxy [37,38], polyamide 6 [39,40] and polypropylene [41]. In self-lubricating composites, as the solid matrix wears, the liquid lubricant is released to the friction surface without external intervention or maintenance, resulting in a signi cant reduction in matrix wear [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the antifriction and wear mechanisms of PVDF composites are shown in Figure 9. On one hand, during the sliding process, under the action of load and frictional contact, the rupture of microcapsules in the PVDF composite results in release of the encapsulated lubricating oil to the friction surface and thus forming an oil lubricating film 32,37,[39][40][41] ; this oil lubricating film separates the contact surfaces, and thereby reducing the friction coefficient and wear rate. On the other hand, the presence of a large amount of wear debris trapped in the cavity of broken microcapsules will be helpful for the decrease of wear rate.…”
Section: Antifriction and Wear Mechanisms Of Pao@psf/pvdf Compositesmentioning
confidence: 99%
“…[33][34][35][36] At this case, microcapsules containing lubricating oil are well known as a novel core-shell additive that enables the incorporation of lubricating oil into polymer matrices. Various related studies have reported amazing effects of the microcapsules in enhancing the tribological properties of different polymers, such as epoxy, 37,38 polyamide 6, 39,40 and polypropylene. 41 During the wearing of solid matrix, the liquid lubricant is released from the selflubricating composites to the friction surface without external intervention or maintenance, resulting in significant reduction in the matrix wear.…”
Section: Introductionmentioning
confidence: 99%
“…Filling the polymer with microcapsules loaded with liquid lubricant can effectively improve its tribological properties. 18 When the microcapsules rupture during repeated friction, the liquid lubricant is released onto the wear surface, significantly reducing both friction coefficient and wear rate. Khun et al 19 prepared microcapsules containing paraffin and developed paraffin microcapsules/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%